Integrasi Model DIKW (Data-Information-Knowledge-Wisdom) dalam Ilmu Falak Berasaskan Kerangka Sains Islam: Integration of the DIKW Model into Astronomy Based on the Islamic Science Framework - Abdul Niri, Mohammaddin; Mohd Saadon, Mohd Hafiz; Mohd Nawawi, Mohd Saiful Anwar; Jamaludin, Mohd Hafiz (Afkar: Jurnal Akidah dan Pemikiran Islam, 2022)
The interconnection of astronomy with various fields of knowledge and different intellectual outcomes in today’s digital era is becoming more apparent. The contemporary advancement of science, technology and innovation (STI) has been the most important catalyst of the interconnection, which is now concentrating on the integration level. Among the current intellectual outcome integrated into astronomy is the DIKW model. The problem is that the integration brings the values derived from the determinism of positivist science and the indeterminism of post-positivist science. It is due to the weakness of the integration process, which is not based on any scientific framework that concerns the values. As such, the main objective of this research is to address the weakness by studying the integration of the DIKW model into astronomy based on the Islamic science framework. Data collection for this study is through library research, while data analysis methods employed inductive, deductive and comparative methods. As a result, the framework of Islamic science was formulated consisting of three components, namely (i) knowledge methodology, (ii) nature’s essence and occasionalism, and (iii) knowledge classification. Thus, the framework addresses the determinism of positivist science through the understanding of occasionalism. Meanwhile, the unguided combination of knowledge caused by the indeterminism of post-positivist science can be organised through a knowledge classification component. The classification guides the difference between Shariah’s complied and praised knowledge from rejected and reprehensible knowledge.